Mapping Educational Role Dimensions Among Chilean Journalism and Mass Communication Educators - Mellado-Ruiz, C (2013)
The challenges and uncertainties that journalism education has historically faced have led to reconsiderations of its approaches, definitions, and functions in society over time. Yet, little attention has been paid to assess how Journalism and Mass Communications (JMC) educators see their roles, as well as individual and contextual factors that influence their orientations. Based on a survey of educators and data collected from JMC schools in Chile, JMC educators’ roles can be grouped into four distinctive categories: the scholarly-oriented, the didactic-oriented, the practiceoriented, and the journalistic-oriented roles. Overall, the orientation that received the greatest support was the practice-oriented, followed by the didactic and the scholarly-oriented. The findings also reveal that education level, job commitment, gender, current professional journalism experience, organization type, school accreditation and the existence of graduate programs are factors that best predict educators’ orientations. © 2013 Taylor & Francis.